GAGASAN PERUBAHAN PERATURAN DAERAH NOMOR 1 TAHUN 2018 TENTANG TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERUSAHAAN DIKAITKAN DENGAN UPAYA PEMBERDAYAAN PEREMPUAN DI KABUPATEN PELALAWAN PROVINSI RIAU - Gustian Maulana; Emilda Firdaus; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The phenomenon of protecting women's rights is the main thing inwomen's empowerment through government policies by giving special attention towomen's empowerment. One of the most important things that can be utilized bythe Regional Government is the existence of Corporate Social and EnvironmentalResponsibility. However, the government program on the use of TJSLP does notspecifically lead to increasing women's empowerment in Pelalawan Regency,even though empowering women through the TJSLP program can foster creativityand quality of independent life and help the family economy, so that the welfare ofthe community will increase. As for the purposes of writing this thesis, namely:First, to find out the weaknesses of Regional Regulation No.1 of 2018 concerningCorporate Social and Environmental Responsibility in relation to efforts toempower women in Pelalawan Regency, Riau Province. Second, to find out aboutthe idea of amending Regional Regulation No.1 of 2018 concerning CorporateSocial and Environmental Responsibility in relation to efforts to empower womenin Pelalawan Regency, Riau Province.This type of research is sociological juridical research, which focuses onfield research. Sources of data used in this study are primary data, secondarydata and tertiary data.From the results of this study it can be concluded that the weakness of thisRegional Regulation is that there are no specific articles related to theimplementation of TJSLP for women's empowerment efforts, a universal meaningof community empowerment, and the inefficiency of corporate socialresponsibility forums. As well as the idea is to clarify the objectives of theRegional Regulation, maximize the TJSLP forum, and optimize the role of womenby participating in the implementation of TJSLP.Keywords: Women's Empowerment - Corporate Social and EnvironmentalResponsibility - Regional Regulation Number 1 of 2018 concerningCorporate Social and Environmental Responsibility